The End Is Only the Beginning: Exploring Endpapers in Picturebook Biographies. - McNair, Jonda C.; Alexander, LaNorris D.; Boyle, Caitlin E.; Brown, Jace; Cornelissen, Ariel; Crossley, Jared S.; McNamara, Emma K.; Thomas, Carrie Anne (Reading Teacher, 2021)
We present a sampling of recently published picturebook biographies with noteworthy endpapers. First, we highlight scholarship related to picturebook biographies and peritextual features. Second, we present examples of three ways endpapers function, using nine picturebook biographies while also incorporating pedagogical suggestions related to the endpapers. Last, we explain the importance of noticing peritextual features in picturebook biographies.